2000
DOI: 10.1152/ajpgi.2000.278.3.g477
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro model of Brunner's gland secretion in the guinea pig duodenum

Abstract: A novel in vitro model that combined functional and morphological techniques was employed to directly examine pathways regulating Brunner's gland secretion in isolation from epithelium. In vitro submucosal preparations were dissected from guinea pig duodenum. A videomicroscopy technique was used to measure changes in luminal diameter of glandular acini as an index of activation of secretion. Carbachol elicited concentration-dependent dilations of the lumen (EC(50) = 2 microM) by activating muscarinic receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 39 publications
6
27
1
Order By: Relevance
“…These results are very similar to our previous reports using video-microscopy real-time recording of the real time changes of dilatation of acini lumen to track secretion [1,6,7] . In those reports, we showed the range of cholinergic stimulation was between 0.1 μmol/L to 10 μmol/L, with EC50 of 2 μmol/L.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are very similar to our previous reports using video-microscopy real-time recording of the real time changes of dilatation of acini lumen to track secretion [1,6,7] . In those reports, we showed the range of cholinergic stimulation was between 0.1 μmol/L to 10 μmol/L, with EC50 of 2 μmol/L.…”
Section: Discussionsupporting
confidence: 92%
“…Brunner's gland acinar cells contain mucin granules in the apical cytoplasm and previous studies have shown that stimulation-evoked dilation of Brunner's gland apical lumen is associated with the deposition of mucin in this space [1] . In the current study, carbachol (1 μmol/L and 6 μmol/L) evoked a dose-dependent dilation of the lumen (Figure 1 A-C).…”
Section: Carbachol Evokes a Dose-dependent Dilatation Of Brunner's Glmentioning
confidence: 90%
See 2 more Smart Citations
“…No acid mucins were observed in the stomach of C. cyanea. Emptying of the acidic stomach contents into the duodenum, along with gastric hydrochloric acid and proteases, creates a threat to the epithelial barrier of the duodenum (Moore et al, 2000). The secretion from Brunner's glands, along with pancreatic, bile and goblet cell secretions in the small intestine, neutralizes gastric hydrochloric acid (Takehana et al, 2000).…”
Section: Tablementioning
confidence: 99%